Kandungan Fe dan Zn pada Beras Pecah Kulit dan Beras Sosoh dari Galur-Galur Padi Toleran Wereng Batang Cokelat - Wage Ratna Rohaeni; Edi Supriadi; Untung Susanto; Tina Dewi Rosahdi (Jurnal Ilmu Pertanian Indonesia, 2016)
In addition to carbohydrates, rice contains other minerals that function to growth and development of vital human organs. On the other hand, the content is influenced by genetic and milling processes. Indonesian Centre of Rice Research (ICRR) has genetic collection resistant to strains of the brown plant hopper (BPH). Genotypes were studied to assemble the pest-resistant varieties with high iron (Fe) and zinc (Zn) content. This study aims to determine the BPH-resistant lines that had high and stable Fe and or  Zn content. The study was conducted in XRF Laboratory, ICRR Sukamandi, West Java in 2015. Fe and Zn were determined by using XRF machine with a system of performance-based X-ray. Total 20 rice lines that resistant to BPH was used Fe and Zn content on brown and polished rice were evaluated duplo. The results showed that milling generally decreased the content of Fe and Zn at rate 56.31% and 20.54%, respectively. The highest Fe content was found in BP19564b-WBC-1-1-4-3 (12.25 ppm), while the highest Zn content in BP19564b-WBC-1-9-8-3 (26.35 ppm). Genotype BP19564b-WBC-1-9-4-2 and BP19564b-WBC-1-9-8-3 exhibited the lowest in reduction Fe and Zn content, respective, from brown to polished rice.